Ensino profissional na Polícia Militar de Minas Gerais: análise do efeito-professor no curso técnico em segurança pública - Helio Hiroshi Hamada (2008)
The studies related to the teacher-efectivenes gain space in so far as the researches on schol improvement advance, highlighting the teacher as the factor that makes the difference in the cognitive process when observed in determined contexts. Thus, under this one theoretical support, the present dissertation tried to identify the effect-teacher in the Technical Course in Public Security of the Military Police of Minas Gerais, in order to understand the aspects that are involved in the formation of the professional of Public Security. The collected data were subjected to a statistical treatment of analysis of variance and use of a model of linear multiple regression, being complemented by the qualitative analysis so as to interpret the phenomenon in further depth. The results of the investigation showed clearly that there are differences of effectiveness between the teachers. They were still identified explicative factors associated to the best performance in the teaching, which can provide an opportunity for the discussion about practices of learning used by the teaching staff